The Effect of Cash Transfers to Schools on Voluntary Contributions - Rosangela Bando (Inter-American Development Bank (IDB), 2014)
School-based management programs aim to improve education outcomes by involving parents in allocation decisions about external funds transferred to the school. This paper explores the effects of two school-based management programs on parental investment in schools via voluntary contributions. One program provides both a cash grant and a matching scheme for privately raised funds. Difference-in-differences estimation shows that parents in richer schools increased voluntary contributions by 28 percent, while parents in poorer schools decreased voluntary contributions by 11 percent. This implies that a matching scheme results in higher inequality in resources available to schools. The second program provides only a cash grant to poor schools. Based on a randomized control, estimation shows that parents use 83 percent of the grant to substitute for voluntary contributions. A cash grant alone for poor schools results in an increase in resources available to the school in less than the cash grant transfer.
hdl:11319/6678
Keywords: D1; H5; I2; O2; 330; Education; investment; parental investment; school based matching; management; school grants; voluntary contributions